Improved Simulations of The Inner Magnetosphere During High Geomagnetic Activity With the RAM‐SCB Model. Issue 6 (21st June 2019) - Engel, Miles A.; Morley, Steven K.; Henderson, Michael G.; Jordanova, Vania K.; Woodroffe, Jesse R.; Mahfuz, Rehana
Abstract: Simulating times of high geomagnetic activity are an important part of the continuing efforts to understand space weather and its impacts on humanity. Recent improvements to the Ring‐current Atmosphere interactions Model with Self‐Consistent magnetic field (RAM‐SCB) have been undertaken, with the purpose of expanding the accuracy and robustness of the model during these highly active times. The improvements include a number of changes to the functionality of both the RAM model and the self‐consistent magnetic field calculation. In addition, the models have been modernized and rewritten in an effort to make them more user friendly and understandable. The effect of these changes is shown by simulating the day of 17 March 2013, which saw Sym‐H drop below −100 nT and included a magnetosphere push‐in within geosynchronous orbit. The comparison between the previous model configuration and this new configuration is investigated by calculating a series of metrics for the relation between the observed and modeled Sym‐H, as well as the >10‐keV electron flux measured by the HOPE and MAGEIS instruments aboard RBSP‐B and the simulated electron flux. These metrics show that the improvements to the model have increased the accuracy of the model for the given simulation. Key Points: The RAM‐SCB inner magnetosphere model has been upgraded to track the magnetopause location and allow it to move inside the RAM‐SCB domain Improvements made to the self consistent magnetic field calculation give a more accurate solution for disturbed configurations The improved model shows improved accuracy and skill for SYM‐H and electron flux at Van Allen Probes for the 17 March 2013 geomagnetic storm